PENGARUH AUDIT INTERNAL DAN KOMITE AUDIT TERHADAP GOOD CORPORATE GOVERNANCE (STUDI KASUS PT. RATEL SHELBY INDONESIA) - Ahmad braja wahyu, Ahmad braja wahyu; Syahputra, Oky; Aristantya, Selvy (Fakultas Ekonomi Prodi Akuntansi, 2025)
This study aims to determine the impact of internal audit and the audit committee on the implementation of Good Corporate Governance at PT. Ratel Shelby Indonesia. The research strategy employs a quantitative method with a descriptive approach. Data analysis is conducted using multiple linear regression with SPSS software version 25.0.2.0. The population for this study is PT. Ratel Shelby Indonesia, with the research sample consisting of parties involved in internal audit practices and the audit committee related to Good Corporate Governance. Sampling is conducted using a non-probability sampling method with convenience sampling technique. Data collection is performed using a questionnaire distributed to respondents including the audit committee, internal audit unit, company secretary, and financial staff. Hypothesis testing is carried out using the coefficient of determination test and t-test. The results of the study demonstrate that internal audit and the audit committee have a positive impact on the implementation of Good Corporate Governance. This indicates that improved internal audit performance and more effective roles of the audit committee can influence the enhancement of Good Corporate Governance. Good internal audit performance and effective oversight by the audit committee will positively affect Good Corporate Governance at PT. Ratel Shelby Indonesia.